PEMBINAAN STUDI KELAYAKAN BISNIS BAGI ANGGOTA PERSATUAN PERANTAU SARIAK SUNGAI ABU (PESSAS) KOTA BATAM - Very Karnadi; Raymond; Dian Lestari Siregar (ASOSIASI IDEBAHASA KEPRI, 2022)
Many MSMEs fail in the initial operational process, one of the reasons for the failure of these MSMEs is the lack of analysis of the feasibility study of the business being carried out. In the process, most of the PESSAs members who work as traders experience many problems in developing and determining the location of the business. For this reason, community service this time is coaching in understanding and making a business feasibility study of a business, the method used in community service this time is first the Lecturer Team gives lectures and explanations about the theory of business feasibility studies, both participants will be given coaching in making business feasibility studies starting from investment costs to socio-economic analysis, the three participants will be given the opportunity to discuss the problems faced in making a business feasibility study. It is hoped that this community service program can contribute in the form of: First, participants are motivated to make business feasibility studies, second, participants are able to be skilled in making business feasibility studies. Based on the guidance that has been carried out by members of PESSAS, they are able to make their own business feasibility studies